BellatorVR: A Virtual Reality Application to Support Firearms Training for Military Police - Abreu, Igor de Sousa; Silva, Luís Fernando Maia Santos (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2025: Anais do LII Seminário Integrado de Software e Hardware, 2025)
This paper presents BellatorVR, a virtual reality application designed to support firearms training, particularly by mitigating risks associated with live weapon use for novice users. The system offers a controlled and immersive environment for realistic weapon handling and tactical practice. Its development included optimized 3D modeling, interaction mechanics, and design patterns to ensure performance and usability. An exploratory pilot study with four participants was conducted to assess feasibility, user interaction, and initial perception. Preliminary feedback indicates that BellatorVR shows potential as a complementary tool for early-stage training, providing valuable insights to guide future development.